2017
DOI: 10.1016/j.actbio.2016.11.060
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cell surface PEGylation and short-course immunotherapy on islet graft survival in an allogeneic murine model

Abstract: Islet transplantation is a promising therapy for Type 1 diabetes mellitus; however, host inflammatory and immune responses lead to islet dysfunction and destruction, despite potent systemic immunosuppression. Grafting of poly(ethylene glycol) (PEG) to the periphery of cells or tissues can mitigate inflammation and immune recognition via generation of a steric barrier. Herein, we sought to evaluate the complementary impact of islet PEGylation with a short-course immunotherapy on the survival of fully-MHC mismat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 79 publications
1
45
0
Order By: Relevance
“…NHP islets were surface modified with linear PEG chains using a protocol optimized and validated in rodent islets . Uniform conjugation of PEG to the islet periphery was observed (Figure A) with no visually distinct differences in morphology or viability when compared to untreated control islets (Figure C‐F).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…NHP islets were surface modified with linear PEG chains using a protocol optimized and validated in rodent islets . Uniform conjugation of PEG to the islet periphery was observed (Figure A) with no visually distinct differences in morphology or viability when compared to untreated control islets (Figure C‐F).…”
Section: Resultsmentioning
confidence: 98%
“…Transplant studies were initiated to determine if the protective effect of islet PEGylation observed in rodent studies would translate to the NHP. Immunosuppression consisted of induction with thymoglobulin and maintenance with tacrolimus for the first month, followed by a transition to rapamycin monotherapy 28 days after transplant (see Figure top schematic).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a PEGylated silicon nanopore membrane to encapsulate islets protects islets from cytokine induced inflammation and destruction in vitro (65). Recently, PEGylation alone provided modest immunosuppression in an allogeneic transplant model (66). Combined with regular delivery of immunosuppressive drugs, mice that received PEGylated islets exhibited long-term normoglycemia.…”
Section: Biosynthetic Materials For Islet Deliverymentioning
confidence: 99%